2021
DOI: 10.5187/jast.2021.e69
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA expression profiling during the suckling-to-weaning transition in pigs

Abstract: MicroRNA expression profiling during the suckling-toweaning transition in pigs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…The miR-10b levels in villus upper cells on days 3 and 7 were significantly lower than that on day 14 post-weaning and strikingly reduced compared to day 0. These findings are consistent with the Jang and Lee [ 22 ] study, which performed microRNA expression profiling during the suckling-to-weaning transition in piglets to identify weaning-associated differentially expressed miRNAs. In that research, the authors found that miR-10a-5p, another member of the highly conserved miR-10 family, had a decreased expression at 1 week after weaning and a stable expression at 2 weeks after weaning.…”
Section: Discussionsupporting
confidence: 91%
“…The miR-10b levels in villus upper cells on days 3 and 7 were significantly lower than that on day 14 post-weaning and strikingly reduced compared to day 0. These findings are consistent with the Jang and Lee [ 22 ] study, which performed microRNA expression profiling during the suckling-to-weaning transition in piglets to identify weaning-associated differentially expressed miRNAs. In that research, the authors found that miR-10a-5p, another member of the highly conserved miR-10 family, had a decreased expression at 1 week after weaning and a stable expression at 2 weeks after weaning.…”
Section: Discussionsupporting
confidence: 91%
“…The intestinal epithelium digests and absorbs nutrients and forms a barrier against pathogens and toxic substances [1,2]. The intestinal epithelium is also important for maintaining health as it is the first physical barrier to detect external substances [3].…”
Section: Introductionmentioning
confidence: 99%
“…EVs consist of various types of biological products, including proteins, lipids, and microRNAs (miRNAs). miRNAs are small nucleic acids ranging from 18 to 22 nucleotides that play a role in regulating posttranscriptional gene regulation and transferring signals into the host ( 15 ). Previous studies have reported that miRNA has been associated with a variety of physiological functions, including the regulation of the immune system ( 16 ).…”
Section: Introductionmentioning
confidence: 99%